Existence of the Mild Solutions for Impulsive Fractional Equations with Infinite Delay - Jaydev Dabas; Archana Chauhan; Mukesh Kumar (International Journal of Differential Equations)
This paper is concerned with the existence and uniqueness of a mild solution of a semilinear fractional-order functional evolution differential equation with the infinite delay and impulsive effects. The existence and uniqueness of a mild solution is established using a solution operator and the classical fixed-point theorems.